On-farm performance of forge crops and assessment of natural pasture productivity in west Shewa zone - Assefa, G.; Gebeyehu, A.; Feyissa, F.; Tekletsadik, T. (Ethiopian Agricultural Research Organization, 2002)
This paper summarizes on-farm research activities on evaluation and demonstrations of some forage species around west Shewa zone. The farmers were provided with forage seeds and demonstrated with the recommended practices demonstrated. They were participated in all the activities from land preparation to forage harvesting and utilization. Individual and group of farmers, and researchers using formal and informal discussion evaluated the trials. Ideas and experiences were shared among Development workers and researchers in different occasions such as field days. Adaptation and forage yield of most forage crops tested were different from the on-station results. Farmers preferred those forage species, which are easy to establish, vigorous and consumed by their animals. Among the tested forage crops, oats, vetch and napier grass were well preformed and chosen by farmers. Since shortage of land is the major problem in the study area, farmers were interested to produce forage crops through strategies, which reduced cropland competition and replenish their resources especially in line with natural resource management. On the other hand, farmers are willing to allocate their arable land for forage production if they are provided with crossbred dairy cows so long as the income from the sale of milk and milk products is rewarding. Farmers who have crossbred animals also grow productive forage crops such as napier grass and fodder beet in their back yards. While cultivating oats-vetch mixture on croplands, farmers were well aware of its benefit in improving the soil fertility. Hence, most farmers have sown either tef or wheat following oats-vetch mixture. The need of improving communal grazing lands through better management and utilization techniques was the question of all farmers. Draining the grazing land, resting and improving species composition are some of the ideas farmers raised to be considered. But the communal way of grazing and low productivity of the indigenous animals doesn't encourage farmers for improvement and limited other interventions. Better extension and Development activities, training and policy interventions may improve the system. Generally farmers showed high interest to develop forage crops if the benefit derived from its production is paying. Hence, conventional forage production is highly acceptable if it is linked with crossbred cows as one of the packages in dairy Development program. On the other hand food-forage crop integration and improvement in the utilization of available feed resources could be useful options to meet the feed demand of local animals, which are mainly emphasized on the provision of drought power for crop land cultivation.